PENGARUH PRODUCT QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PENGGUNA iPHONE DI SURABAYA - Steven Benedictus Darmono (Jurnal Strategi Pemasaran, 2020)
This research was conducted to determine the effect of Product Quality on Customer Loyalty with Customer Satisfaction as an intervening variable on iPhone users in Surabaya. This type of research used in this study is causal quantitative using the SmartPLS program. Respondents in this study are iPhone users in Surabaya, with 200 respondents using purposive sampling technique combined with Cluster. The data collection technique in this study was a questionnaire through Google Form. The results of this study found that Product Quality has a positive and significant effect on Customer Loyalty, Product Quality has a positive and significant effect on Customer Satisfaction, Customer Satisfaction has a positive and significant effect on Customer Loyalty.